Identification of plant consumption in two mummies chancay (Peru) through the study of dental scarce - Correa-Trigoso, Denis E.; Universidad Nacional de Trujillo (2021)
This article presents the results of the study of plant microrests (starch grains, plant tissues and silicophytites) registered in dental tartar from two chancay mummies belonging to the Museum of Natural and Cultural History of the Private University Antenor Orrego, in the city of Trujillo, north coast of Peru. Research problems are associated with identifying which vegetables were consumed by the two chancay mummies and understanding the social implications of the use of these plants. The methodology for the analysis of the starch grains was the disaggregation of the dental calculus and the removal of organic matter, with the aim of isolating the micro-remains to be analyzed according to their morphology and taxonomically identifying them. It was established that the two individuals consumed nine species of vegetables and that they placed cotton fiber inside their mouths when they were buried, as part of a Chancay funeral pattern.